13-degree impact test of long-fiber-reinforced thermoplastic composite wheel manufactured by injection molding–Improved co-simulation approach and experimental investigation. (April 2023) - Zhang, Yue; Liu, Xiandong; He, Tian; Wan, Xiaofei; Shan, Yingchun
Highlights: An improved co-simulation for the impact test of injection-molded composite wheel is proposed. The composite wheels are injection molded and the impact test is conducted to verify the method. Compared with the existing methods, the improved version gives much more accurate results. Achieving the match state between the two types of mesh models improves the simulation results. The wheel's impact resistance varies with tires used, but no consistent rules can be followed. Abstract: The excellent mechanical properties, ease of processability and intrinsic recyclability drive the long-fiber-reinforced thermoplastic composite to be recognized as a potential alternative material. And combined with injection molding process, a new path to promote the lightweight design of automobile wheels may be opened up. At present, some numerical methods of 13-degree impact test have been proposed to evaluate the mechanical performance of such composite wheels, but the simulation accuracy is insufficient arising from the following drawbacks to provide a reliable basis for the optimal design. Specifically, the one is to use the simplified tire model to evaluate its effect on the impact resistance of wheel, and the other is that during establishing the anisotropic material model of composite wheel by using the mapped fiber orientation information, the finite element mesh model for injection molding analysis is not matched with the one for structural analysis. Aiming at these problems, an improved co-simulation method is proposed to more accurately predict the impact performance of such wheels. Then, the long-glass-fiber reinforced polyamide 66 composite wheels are fabricated through injection molding process and the corresponding impact test is performed to verify the validity of this approach. And compared with the existing co-simulation method, the calculation accuracy of this improved version is obviously increased. Besides, the effects of these improvements on the simulation results are comparatively analyzed, and the influence of different actual tires on the impact performance of wheel is also investigated by test. The results show that, whether or not to achieve the match state between the two types of mesh models significantly affects the final impact simulation results, and the impact performance of composite wheel varies obviously with different tires used but no consistent rule can be followed.